Google Translate on Grab Application: Translation Study - Niswatin Nurul Hidayati (PANYONARA: Journal of English Education, 2021)
The Google Translate service is widely used in Indonesia because it is considered very helpful, including being used by the Grab application platform, which the public has increasingly used in recent years. This research focused on the study of translation used in conversations between drivers and consumers. There were indeed many kinds of research on translation, but not many have discussed the translation used on Grab platforms. This research aimed to describe some of the translation styles used and deemed necessary for Grab and Google Translate improvement. Researchers used a qualitative approach by presenting data in the form of descriptions and analysis. Several points were found to be improved in the process of translating sentences in the grab application, including omitting the translation into the target language, word by word translation, inconsistency in translating a term, the application was unable to detect abbreviations, so it was not translated, the interrogative sentence in the source language was translated into a statement sentence in the target language. This research had many limitations so that other researchers can develop it more widely in the future.